ANALISIS PERUBAHAN KETEBALAN PIPA AKIBAT PENGARUH KOROSI DAN SISA UMUR PAKAI PIPA DI PLTD NAMLEA KABUPATEN BURU - Ahmad Zulfikri Pratama; Erwin B. Pattikayhattu; Edison Effendy (Department of Mechanical Engineering, 2024)
In modern industry, pipelines play an important role, especially in the oil and gas sector. Pipes are susceptible to corrosion, especially those in aggressive environments such as PLTD Namlea, which is directly adjacent to the coast. Corrosion, as a natural process of metal degradation, is inevitable, but it can be controlled to extend the life of the pipe. This study measured the thickness of the pipes at PLTD Namlea using Ultrasonic Testing (UT) to determine the corrosion rate and remaining service life. Based on measurements, the minimum thickness of pipes at various measuring points (Measuring Points / MP) still meets the API 574 standard, which must not be less than 1.8 mm. The average corrosion rate ranges from 0.336 to 0.358 mm/year. These values affect the rate of degradation of the pipe and the remaining service life, which ranges from 5.5 to 6.1 years at various measurement points. Pipes that have a higher corrosion rate will have a shorter remaining service life. Overall, the pipeline at PLTD Namlea is still laid. Keywords: Pipe, Corrosion Rate, Remaining Life